Women equity in tourism: Analysis of gender equality in Tukad Bindu tourism objects - Putra, I Putu Adi Permana (Pusat Studi Gender dan Anak, 2024)
Gender exists as a social construction that often positions women as secondary and has become an issue that has attracted quite a lot of public attention. Gender equity and equality must be pursued in social development, especially tourism management and development. This effort is to develop and strengthen the nation's progress in supporting gender equality in every line of life. This study aims to describe and analyze women's participation in the management of the Tukad Bindu tourist attraction and explore the equity and equality obtained by women in tourism development. The methodology used in this research is a qualitative-descriptive approach. The data collection techniques were non-participatory observation, in-depth interviews with key informants, documentation, and a literature study. Informants were determined using a purposive sampling technique. Data analysis was carried out using qualitative data analysis techniques. This research also uses data triangulation techniques to test the validity of the data. The research results show that women have a role and contribution to the management and development of the Tukad Bindu tourist attraction. Women have been given access to participate in public spaces, especially tourism management. However, the access that women have is quite limited, so women's participation and control roles are limited. This reality shows that gender equity and equality are not optimal in community-based tourism due to hegemony, which causes gender bias in tourism development.